2021
DOI: 10.3389/fpsyg.2021.694927
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and Novelty in Aesthetic Preference: The Effects of the Properties of the Artwork and the Beholder

Abstract: Familiarity and novelty are fundamental yet competing factors influencing aesthetic preference. However, whether people prefer familiar paintings or novel paintings has not been clear. Using both behavioral and eye-tracking measures, the present study aimed to investigate whether the effect of familiarity-novelty on aesthetic preference is independent or dependent on artwork properties (painting content, visual complexity) and viewer characteristics (experience in art). Participants were presented with two ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 117 publications
(185 reference statements)
0
13
0
Order By: Relevance
“…Research has indicated that more familiar faces are perceived as more positive, and are also more liked, than unfamiliar faces (Carr et al, 2017;Claypool et al, 2007). Moreover, familiar artworks are often preferred to less familiar ones, having similar valence and arousal ratings (Song et al, 2021;Van Paasschen et al, 2015). Such results can be explained within the framework of the mere exposure effect, indicating that previously encountered stimuli, hence being more familiar, are preferred to the novel ones (Zajonc, 1968).…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…Research has indicated that more familiar faces are perceived as more positive, and are also more liked, than unfamiliar faces (Carr et al, 2017;Claypool et al, 2007). Moreover, familiar artworks are often preferred to less familiar ones, having similar valence and arousal ratings (Song et al, 2021;Van Paasschen et al, 2015). Such results can be explained within the framework of the mere exposure effect, indicating that previously encountered stimuli, hence being more familiar, are preferred to the novel ones (Zajonc, 1968).…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…Importantly, it seems plausible that potential well-being effects of restorative environments would be stronger if people spend more time in them; thus, we tested whether longer times with the multimodal arts would increase this effect. Based on evidence that people look longer at stimuli they like, prefer, or find beautiful (Glaholt & Reingold, 2009;Goller et al, 2019;Holmes & Zanker, 2012;Leder et al, 2010Leder et al, , 2016, and that this effect also holds for visual artworks (Plumhoff & Schirillo, 2009;Song et al, 2021) cross-culturally (Mikuni et al, 2022), we assume that multimodal art experiences would lead to longer viewing times and reduce (mental) fatigue.…”
Section: Fatigue Viewing Time and Aesthetic Experiencementioning
confidence: 99%
“…Nevertheless, there is still great diversity in the average observers' aesthetic appreciation of (dance) stimuli. Some observers prefer more surprising and chaotic stimuli than others, and some prefer a harmonious balance of known and unknown stimuli (Berlyne, 1974;Song et al, 2021). However, research indicates that observers' expertise in dance is essential in perceiving dance performances' aesthetics (Calvo-Merino et al, 2010;Glass, 2005;Kirsch et al, 2013;Vinken & Heinen, 2022).…”
Section: Introductionmentioning
confidence: 99%